2018
DOI: 10.5194/gmd-11-959-2018
|View full text |Cite
|
Sign up to set email alerts
|

Global high-resolution simulations of tropospheric nitrogen dioxide using CHASER V4.0

Abstract: Abstract. We evaluate global tropospheric nitrogen dioxide (NO 2 ) simulations using the CHASER V4.0 global chemical transport model (CTM) at horizontal resolutions of 0.56, 1.1, and 2.8 • . Model evaluation was conducted using satellite tropospheric NO 2 retrievals from the Ozone Monitoring Instrument (OMI) and the Global Ozone Monitoring Experiment-2 (GOME-2) and aircraft observations from the 2014 Front Range Air Pollution and Photochemistry Experiment (FRAPPÉ). Agreement against satellite retrievals improv… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
58
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 38 publications
(66 citation statements)
references
References 109 publications
(130 reference statements)
1
58
1
Order By: Relevance
“…A high-resolution version of the MIROC-Chem model with a horizontal resolution of T106 (1.1 • × 1.1 • ) was used. Sekiya et al (2018) demonstrated the improved model performance on tropospheric ozone and its precursors by increasing the model resolution from 2.8…”
Section: Updated Tropospheric Chemistry Reanalysis (Tcr-2)mentioning
confidence: 98%
See 1 more Smart Citation
“…A high-resolution version of the MIROC-Chem model with a horizontal resolution of T106 (1.1 • × 1.1 • ) was used. Sekiya et al (2018) demonstrated the improved model performance on tropospheric ozone and its precursors by increasing the model resolution from 2.8…”
Section: Updated Tropospheric Chemistry Reanalysis (Tcr-2)mentioning
confidence: 98%
“…Anthropogenic emissions originate essentially from the MACCity inventory (Granier et al, 2011) with enhanced wintertime CO emissions over Europe and the US (Stein et al, 2014). Monthly specific biogenic emissions originate from MEGAN-MACC (Sindelarova et al, 2014) but using monthly climatological values from 2011 onwards. Daily biomass-burning emissions originate from GFASv1.2 (Kaiser et al, 2013).…”
Section: The Cams Interim Reanalysismentioning
confidence: 99%
“…A high-resolution version of the MIROC-Chem model with a horizontal resolution of T106 (1.1° x 1.1°) was used. Sekiya et al (2018) (Graedel et al, 1993) for NOx. Emission data for other compounds are taken from the HTAP version 2 and GFED version 4 inventories.…”
Section: Updated Tropospheric Chemistry Reanalysis (Tcr-2)mentioning
confidence: 99%
“…The horizontal resolution corresponds to that of IASI, using for each pixel the UV measurements from the closest GOME-2 pixel (without averaging). Spectra and Jacobians in the IR and UV are respectively simulated by the KOPRA (Karlsruhe Optimized and Precise Radiative transfer Algorithm; Stiller et al, 2002) and VLIDORT (Vector Linearized Discrete Ordinate Radiative Transfer;Spurr, 2006) radiative transfer codes. The effects of clouds and aerosols are partially taken into account by iteratively adjusting offsets for each of the seven spectral microwindows (between 980 and 1070 cm −1 ) used in the IR and effective surface albedos and cloud fractions in the UV (two micro-windows between 290 and 345 nm).…”
Section: Dataset Descriptionmentioning
confidence: 99%